Bone density in competitive cyclists: a longitudinal assessment across the cycling season - Baker, Breanne S., author; Reiser, Raoul F., II, advisor; Browning, Raymond, committee member; Puttlitz, Christian, committee member (Colorado State University. Libraries, 2015)
The purpose of this study was to investigate in a relatively large group of competitive cyclists how sex, competition level and type of racing influenced bone mineral density (BMD) and bone mineral content (BMC) at the beginning of the season and changes that occurred during the season. In total, 42 participants (22 males and 20 females) completed the study. Subjects were stratified by sex, USA Cycling Category and racing type. At the beginning of the season in February, participants were asked to complete a health history questionnaire, four day dietary log and a DXA scan. After a mean of 180 days participants completed another visit. At the beginning of the season significant differences were found between the groups. Pre-season sex differences were seen for height, Body Mass, Body Fat %, Lean Mass %, Lower Body (LB) BMCg, Upper Body (UB) BMCg, Shank BMD and estimated number of pre-season training (p≤0.015). Differences between Cat. 1 and Cat. 4 riders were observed for age and UB BMCg (p≤0.019). The number of years’ experience cycling and racing and the estimated number of races were significant pre-season difference between type of racing (p=0.019). BMD T Score was not significantly different between sexes, Cat. or type of racing and did not significantly increase over the season (p≥0.053). Further analysis shows a wide variety of positive and negative correlates of skeletal health that deserve further investigation such as age, body composition measures, diet and time spent cycling. This study suggests that cycling is not detrimental to BMD over a competitive season.